Impact of ‘brown envelope journalism’ on news coverage in Ghana - Acheampong, Richmond (Yayasan Mitra Persada Nusantara, 2024)
The study looked at how ‘Brown Envelope Journalism’ affects news coverage in Ghana. It also determined whether journalists in Ghana have the necessary ethics training to fend off the allure of brown envelopes and how the presence of brown envelope journalism impacts the public's confidence in Ghana's media. A questionnaire with 17 data-collection items was distributed randomly to 300 journalists in the Sunyani Municipality in Ghana’s Bono Region. The majority of journalists (i.e., 83%) said ‘Brown Envelope Journalism’ causes the underreporting of some important issues or the overemphasis of others, while 17% of them, the minority respondents, said ‘Brown Envelope Journalism’ does not cause the underreporting of important issues or the overemphasis of others. Based on the findings of the study, it was recommended among other things that to eradicate ‘Brown Envelope Journalism’ from Ghana's media landscape, Ghanaian media organizations should pay their journalists well.